Inequitable Distribution of FTP Marketing by Neighborhood Characteristics: Further Evidence for Targeted Marketing. Issue 4 (23rd October 2021) - Rose, Shyanika W; Anesetti-Rothermel, Andrew; Westneat, Susan; van de Venne, Judy; Folger, Shanell; Rahman, Basmah; Azam, Tofial; Zhou, Yitong; Debnam, Charles; Ribisl, Kurt; Cohn, Amy M
Abstract: Introduction: Flavored tobacco products (FTPs) are disproportionately used among young people and racial/ethnic minority populations. However, few studies have examined the retail distribution of such product marketing beyond menthol cigarettes. This study created geographic-based predictions about marketing of FTPs (overall, cigarettes, cigars, e-cigarettes, and smokeless) in stores across Washington, DC neighborhoods. We examined neighborhood-level demographic correlates of the amount of FTP and non-FTP marketing. Methods: We conducted photographic audits of interior and exterior tobacco marketing in 96 Washington, DC tobacco retailers visited by 149 young adult respondents between 2018–2019. We created a geographic predictive surface of overall and product-specific tobacco marketing and then estimated the average predicted amount of marketing at the census-tract level using zonal statistics. Using linear regression, we examined neighborhood demographic correlates (race/ethnicity, family poverty, and youth population under 18) of FTP and non-FTP marketing. Results: The predicted amount of non-FTP ads/displays were evenly distributed with no neighborhood variability (Range 8.46–8.46). FTP marketing overall was geographically concentrated with greater range across neighborhoods (Range 6.27–16.77). Greater FTP marketing overall and flavored cigar marketing was available in neighborhoods with higher percentages of Black residents. Flavored cigar marketing was less available in neighborhoods with more Hispanic residents, but there was greater flavored smokeless tobacco marketing. Nonflavored marketing overall and by product did not vary across neighborhoods. Conclusions: This study provides evidence of disproportionate distribution of FTP marketing in Black neighborhoods, especially for flavored cigars, at the point-of-sale. Policies that restrict the sale of FTPs may enhance health equity. Implications: Tobacco marketing has frequently been shown to be more prevalent in neighborhoods with lower household income and more Black residents. Using geographic-based predictions, we find that greater flavored tobacco marketing in these neighborhoods, not decreased marketing for nonflavored tobacco, is driving this disparity. Targeting Black neighborhoods with increased marketing of flavored tobacco products, which has been found to be more appealing, easier to use, and harder to quit is a social justice issue.